Development and Validation of Farmer’s Attitude Scale towards Anand Agricultural University (Indian Journal of Extension Education, 2023)
Anand Agricultural University is a premier agricultural university in India. The purpose of this study was to develop a valid and reliable instrument for assessing farmers’ attitudes toward Anand Agricultural University. The scale product method was used to construct the scale. It is a hybrid of the Likert and Thurstone techniques. A comprehensive list of 33 statements was prepared and finally, 26 statements were selected as they were found to be non-ambiguous. Based on the S value and Q value, 14 statements including 11 positive statements and 3 negative statements were chosen to construct a scale that would assess the attitude of farmers towards Anand Agricultural University. The scale was found reliable, with a reliability coefficient (0.827). The scale’s validity was evaluated using expert judgment. This scale may be used to measure farmers’ attitudes towards similar institutions or domains with suitable modifications.